The Role of Gender Diversity in Moderating the Impact of Intellectual Capital on the Performance of Islamic Banks - Ridha, M. Arsyadi (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to analyze the effect of intellectual capital components, namely Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE), on the performance of Islamic banks, as well as to examine the moderating role of gender diversity in Islamic banking governance. This study uses a quantitative design with a panel data approach, covering 14 Islamic commercial banks in Indonesia during the period 2017–2022, and analyzed using moderated regression analysis. The results show that HCE and CEE have a positive effect on Islamic bank performance, while SCE has a negative effect. Furthermore, gender diversity was found to moderate the relationship between intellectual capital and bank performance, with a positive moderating effect on the SCE–performance and CEE–performance relationships, but a negative moderating effect on the HCE–performance relationship. These findings indicate that gender diversity can strengthen governance effectiveness and financial efficiency, but the optimization of human capital is still influenced by organizational factors and cultural context. The policy implications of this study emphasize the importance of formulating governance strategies that not only encourage increased gender diversity at the board level but also ensure the alignment of roles and the effective utilization of intellectual capital in Islamic banking. The limitations of this study lie in the use of specific measures of intellectual capital and its focus on the context of Islamic banking in Indonesia. Therefore, further research is recommended to use alternative proxies and consider cross-country institutional factors.